2011
DOI: 10.1051/0004-6361/201014738
|View full text |Cite
|
Sign up to set email alerts
|

Dark matter interpretation of the origin of non-thermal phenomena in galaxy clusters

Abstract: Aims. We studied the multi-frequency predictions of various annihilating dark matter (DM) scenarios in order to explore the possibility to interpret the still unknown origin of non-thermal phenomena in galaxy clusters. Methods. We consider three different DM models with light (9 GeV), intermediate (60 GeV), and high (500 GeV) neutralino mass and study their physical effects in the atmosphere of the Coma cluster. The secondary particles created in the neutralino annihilation processes produce a multi-frequency … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 78 publications
3
25
0
Order By: Relevance
“…In this calculation, we assume different masses and compositions for the neutralino by using the DarkSusy package (Gondolo et al 2004). We assume here a boosting factor due to the subhalos DM distribution (Pieri et al 2011) equal to 1, and larger values can be considered eventually simply by multiplying the result by this factor (see, e.g., Colafrancesco et al 2011b).…”
Section: The Dark Matter Eastern Peakmentioning
confidence: 99%
See 1 more Smart Citation
“…In this calculation, we assume different masses and compositions for the neutralino by using the DarkSusy package (Gondolo et al 2004). We assume here a boosting factor due to the subhalos DM distribution (Pieri et al 2011) equal to 1, and larger values can be considered eventually simply by multiplying the result by this factor (see, e.g., Colafrancesco et al 2011b).…”
Section: The Dark Matter Eastern Peakmentioning
confidence: 99%
“…Synchrotron emission from electrons either primarily accelerated at shocks (Tribble 1993) or re-accelerated by turbulence (Brunetti et al 2001), or secondarily produced by proton-proton collisions (Blasi & Colafrancesco 1999) or DM annihilation (Colafrancesco & Mele 2001, Colafrancesco et al 2006, 2011b) is expected to be observed in the radio band. The same primary and/or secondary electrons are also expected to emit by inverse Compton Scattering (ICS) off the Cosmic Microwave Background (CMB) photons (and possibly other cosmic backgrounds), and by non-thermal bremsstrahlung off the nuclei of the thermal gas over a wide energy range from ultraviolet to gamma-rays (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies of the synchrotron radio emission originating from DMproduced electrons in galaxy clusters [1,2,3,4] have shown that these models can naturally reproduce the observed steepening of the integrated flux spectrum of the Coma cluster at high frequencies (ν ∼ > 1.4 GHz) for realistic values of the magnetic field (i.e., B ∼ 0.1 − 5 µG) in the case of light neutralino DM particles (with mass M χ ∼ 10 − 40 GeV), but they cannot reproduce the observed shape of the radio surface brightness, unless one assumes a magnetic field increasing with radius, that is however excluded by recent observations [5]. Another argument against the simple DM interpretation of the origin of non-thermal electrons in galaxy clusters is given by the recent limits on the DM annihilation cross section obtained with Fermi-LAT through measures in galaxy clusters [6], in dwarf galaxies [7], and in the Galactic center [8], as well as with Planck from the CMB analysis [9]; these results point, in fact, to values of the annihilation cross section upper limits of the order of σv ∼ 10 −27 − 10 −26 cm 3 s −1 , whereas the values required to fit the radio halo flux are of the order of 10 −25 cm 3 s −1 or higher (see, e.g., [3]). This gap is smaller if the results of another interpretation of the gamma-ray excess measured by Fermi-LAT in the Galactic center [10] are considered: in this last work, best fit values of the annihilation cross section of 2.2 × 10 −26 cm 3 s −1 and 7.4 × 10 −26 cm 3 s −1 for neutralino mass of 9 GeV (with τ + τ − composition) and 43 GeV (with bb composition) have been found, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…We compute the expected flux for synchrotron emission processes from DM annihilation by dividing a cluster of dimension 2 Mpc into cubes of size 10 kpc. We based our studies of radio emission from DM annihilation processes by taking neutralinos to be primarily and dominantly composed of bb species and/or light and intermediate DM mass models as in [10]. We consider neutralino masses M χ of 35 and 60 GeV, and we take the velocity averaged annihilation cross-section, < σV >, of 1.0 × 10 −26 cm 3 s −1 from Fermi upper limit.…”
Section: Resultsmentioning
confidence: 99%